Perbedaan Tingkat Kepuasan Pasien Bpjs Dan Non Bpjs Pada Mutu Pelayanan Pendaftaran Rumah Sakit Pusat Angkatan Udara Dr. S. Hardjolukito Bantul - Ozzi Annisa, Zarra; , Ibnu Mardioko, SKM.,MM; , Anisa Catur Wijayanti, SKM.,M.Epid (2016)
Zarra Ozzi Annisa J410131039 DIFFERENCES OF PATIENT SATISFACTION BPJS AND NON BPJS ON QUALITY OF SERVICE REGISTRATION OF RSPAU dr. S. HARDJOLUKITO BANTUL ABSTRACT The hospital as a public service institutions that are affected by the development of health science, technological progress and socio-economic life of society should be able to improve service quality and satisfy customers. The purpose of this study was to determine differences in the level of patient satisfaction BPJS and non BPJS on service quality registration section RSPAU dr. S. Hardjolukito Bantul. The inductive method comparative study with cross sectional approach. The population is to use the average stay of patients enrolled in regristation of 523 patients, how sampling by proportional sampling of 202 respondents. Statistical test using the Mann-Whitney U Test with the help of statistical program on the computer. The results showed that there are differences in the level of patient satisfaction with the level of patient satisfaction BPJS and non BPJS in RSPAU dr. S. Hardjolukito (p value = 0.000) Keywords: Satisfaction, Patient BPJS and Non BPJS, Quality of Service